Review of Delta, Theta, Alpha, Beta, and Gamma response oscillations in neuropsychiatric disorders - Güntekin, Bahar; BAŞAR, EROL (My University, 2013)
Method and concepts of brain oscillations pervade the neuroscience literature, especially in cognitive processes. Electrophysiological changes in patients with cognitive impairment will provide fundamental knowledge, not only for clinical studies but also, in turn, for understanding cognitive processes in healthy subjects. This review includes description of brain oscillations in schizophrenia, bipolar disorder, mild cognitive impairment, Alzheimer's disease, and attention deficit hyperactivity disorder. The reviewed publications include several methodological approaches: analysis of spontaneous electroencephalogram (EEG) spectra, evoked oscillations, event-related oscillations, and coherences both in spontaneous EEG and event-related oscillations. The review clearly shows that, in cognitive impairment, fundamental changes are observed in all diseases under study. Accordingly, oscillations can most probably be used as biomarkers in clinical studies. The conclusions of this review include several remarks indicating the nature of brain oscillations, their application to cognitive processes, and the usefulness of recording brain oscillations in memory loss, attention deficit, and learning.